CARDIOPSYCHIATRY. A CLASH OF OPINIONS - M. Yu. Drobizhev (Кардиоваскулярная терапия и профилактика)
The article is focused on the novel and former psychiatric disorders (PD) classification in cardiopsychiatry. Novel classification relates PD to the mechanisms of stress. It takes into consideration that stress mechanisms might influence the risk of development and/or progression of cardiovascular diseases (CVD). Former classification is based upon the list of hardly related terms and includes doubtful and outdated diagnoses. It does not explain the pathways of PD influence of CVD. The traditional and recent viewpoints are considered in PD, as the drugs prescription. In a range of cases, PD develop due to neuronal activity dysfunction, hence the selection of drug relates on its ability to influence these disorders. In other cases PD pathogenesis is not known, and drugs are prescribed with unknown influence on neuronal activity.